Impacts of sea cucumber farming on biogeochemical characteristics in the Yellow River estuary, Northern China - Fu, Jing; Yokoyama, Hisashi; Cui, Baoshan; Zhou, Jin; Yan, Jiaguo; Ma, Xu; Shibata, Shozo (Physics and Chemistry of the Earth, Parts A/B/C, 2017)
To investigate the potential environmental effects of pond farming for Apostichopus japonicas in Yellow River estuary, we examined discrepancies of distance-based typical pollution indicators (TOC, TN, NO3−, NH4+, NO2− and PO43−) and biochemical tracers (δ13C and δ15N) in water column and sediment, as well as dietary characteristics of dominant macrobenthos between farming and non-farming areas. The results revealed that studied variables in water column showed no uniform spatial differences. Meanwhile, those in sediment displayed similar decrease tendencies from farming pond to the adjacent tidal flat, which was considered to represent the environmental effects of farming. Biochemical tracers (δ13C and δ15N) in both water column and sediment confirmed the origin of organic matters from the aquaculture waste. The detectable dispersion distance of aquaculture waste was restricted to an area within 50 m distance as determined by most variables in sediment (TOC, TN, NO3− and NH4+), particularly by C:N ratio and δ13C with which origins of the wastes were traced. Bayesian mixing models indicated that in the farming area BMA had a larger contribution, while POM(marine) showed a smaller contribution to the diets of Helice tridens and Macrophthalmus abbreviates compared to those in the non-farming area. The overall results showed that pond farming for Apostichopus japonicus in the Yellow River estuary altered the local environment to a certain extent. For methodological consideration, sediment biogeochemical characteristics as a historical recorder much more effectively reflected aquaculture waste accumulation, and stable isotope approaches are efficient in tracing the origin and extent of various allogenous sources. •Sediment biogeochemical characteristics are effective indices for estimation of sea cucumber pond aquaculture impact.•Dispersion distance of aquaculture waste is restricted within a distance.•Stable isotope approaches are efficient in tracing aquaculture waste in environment.